New models for South African consumption, house prices, and mortgage and non-mortgage debt: Insights for financial stability and monetary transmission - Janine Aron; John Muellbauer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2025)
Aggregate consumption typically exceeds 60 per cent of GDP and should be pivotal in central bank policy models. Most use semi-structural macro-models, yet consumption is usually inadequately specified. We use a systems approach to estimate new equations for South African consumption, house prices, mortgage and non-mortgage debt, and income forecasting. A creditaugmented consumption function approach introduces a greater role for uncertainty and a key role for credit conditions, and varies the spendability of different wealth components. This provides new insights into the multiple monetary transmission mechanisms, from policy interest rates and credit conditions to aggregate demand, including via non-homogeneous household balance sheet items on consumption. Credit conditions for mortgages and for other debt move quite differently from each other, with implications for consumer spending. Non-mortgage debt covers a larger fraction of total household debt than in advanced market economies, affecting household financial vulnerability. Housing market participants tend to extrapolate recent house price changes when forming expectations of capital gains, so positive shocks to housing demand can feed back onto house prices and consumption and extend boom conditions. House prices and debt can overshoot relative to their fundamentals, affecting financial stability. These findings should benefit future policy modelling in South Africa.
Keywords: C32; E21; E51; E58; 330; aggregate consumption; house prices; credit conditions; household debt; housing collateral; monetary transmission; equation system